A new species Cyrtandra sect. Whitia (Gesneriaceae) from Sulawesi, Indonesia - Ahmad, Roland P.p.; Atria, Mega; Kartonegoro, Abdulrokhman (Phytotaxa, 2026)
A species of Cyrtandra sect. Whitia (Blume) Clarke (Gesneriaceae) from Sulawesi, Indonesia is newly described and illustrated. The species was discovered as a climbing epiphytic shrubs in lower montane forest from Central Sulawesi Province. The new species is most similar to C. angularis Elmer in being an epiphytic climber with asymmetric, succulent, and anisophyllous leaves. But differing in bract shape (lanceolate in C. intermedia vs ovate in C. angularis). calyx lobes (3–4 lobes in. C. intermedia vs 3–5 lobes in. C. angularis) pedicels longer (4–7 mm in C. intermedia vs. ca. 0.5 mm in C. angularis), and anthers hair (glabrous anthers in C. intermedia vs. glandular hairy anthers in C. angularis). Full description with colour plates, illustrated, and distribution map are provided. According to the Guidelines for using IUCN Red List Categories and Criteria, the conservation status of new species is assessed as Data Deficient (DD).